Tiny houses desirable or disruptive?. Issue 3 (2nd October 2018) - Brokenshire, Stephanie
ABSTRACT: What happens when tiny houses on wheels [THOW] disrupt the foundations on which we have built our planning and building industry? The very concept of a house being a transportable product seems to defy the planning and building framework we have constructed around our housing industry for decades. But rather than seeing them as disruptive and challenging, THOW could be a solution we've all been searching for to the wicked problem of affordable housing. In recent decades, the tiny house movement has flourished in Europe and America, with an industry of builders, designers, real estate agents and property owners tapping into the tiny economy. The establishment of Australian companies specialising in THOW shows there is a need for planning to catch up with market demand as houses are being constructed, yet certainty of obtaining approval varies considerably between local governments. A combination of planning, building and transport regulations are the largest barriers restricting the growth of THOW as an acceptable housing form in Australia. If tenancy of THOW can be legitimised through planning or building approvals, then regulatory red tape and various economic barriers such as the ability to obtain financing and insurance for THOW may be ameliorated.